2005
DOI: 10.1007/s00595-005-3072-x
|View full text |Cite
|
Sign up to set email alerts
|

Basaloid Carcinoma of the Thymus: Report of a Case

Abstract: We report a case of basaloid carcinoma of the thymus, confirmed by histopathological examination, in a 52-year-old man who underwent complete resection. Local recurrence and lung metastases developed, which were obliterated by radiation therapy. The patient survived for 81 months after surgery. We reviewed the 13 other cases of basaloid carcinoma of the thymus reported in the literature. Presumably, this tumor is radiosensitive and its metastatic route is blood-borne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…No death from the tumor was reported in the English literature until 2006, and the prognosis of the patients with thymic basaloid carcinoma was generally considered to be favorable. However, Morisaki et al 9 in 2006 and Brown et al 11 in 2009 reported cases of deaths from these tumors. The latter reported a minimum of 42% (5/12) of patients to die of the disease.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…No death from the tumor was reported in the English literature until 2006, and the prognosis of the patients with thymic basaloid carcinoma was generally considered to be favorable. However, Morisaki et al 9 in 2006 and Brown et al 11 in 2009 reported cases of deaths from these tumors. The latter reported a minimum of 42% (5/12) of patients to die of the disease.…”
Section: Discussionmentioning
confidence: 94%
“…2-6,10,11 Alternatively, case reports from Japan, 7-9,12-19 although most of them were written in Japanese, [12][13][14][15][16][17][18][19] described the treatment, surgical procedure, recurrence, and prognosis in detail. [7][8][9]13,[15][16][17][18][19] Table 1 shows the median age of the patients to be 59 years (range, 34-77 years); there was a predominance of male patients (24/35, 69%), the average tumor size (including concomitant cyst) was 8.4 cm (range, 2.8-20 cm), most surgical interventions were accompanied by a combined resection of adjacent structures, and 10 out of 27 patients (37%), whose prognoses were recognized, died. No death from the tumor was reported in the English literature until 2006, and the prognosis of the patients with thymic basaloid carcinoma was generally considered to be favorable.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[3][4][5][6][7][8][9][10] Moreover, it obviously has malignant characteristics, with metastasis developing in distant sites such as the lung. 13 In this case, we detected a huge mediastinal tumor invading other organs and performed tumor resection through a median sternotomy because we suspected malignancy with invasion of the surrounding tissue. As was evident in this and other cases of basaloid carcinoma, a mediastinal cystic tumor with MTC can be ruled out, but complete tumor resection is often complicated by aggressive adhesion to the surrounding tissue.…”
Section: Discussionmentioning
confidence: 94%